PATI UMBI SUWEG TERMODIFIKASI SEBAGAI BIOSORBEN PENYERAP ION TIMBAL - Ajeng Yulianti Dwi Lestari; Muhammad Fachmi Kurniawan; Mentari Ferdini Siregar (Faculty of Industrial Technology Universitas Islam Indonesia, 2016)
Novel adsorbents are succesfully manufactured from Amorphophallus campanulatus (Porang or Suweg or Elephant Foot Yam or Foot Yam) starch. The experiment focused on detailing those morphologies and chemical bonds. Analysis with FTIR and SEM showed that PTM sample is the best adsorbent which has most stable of chemical bonding and also has more pores that influence lead adsorption phenomena